Pengaruh Promosi, Lokasi, Dan Harga Terhadap Keputusan Orang Tua Untuk Menyekolahkan Anak Di SD Yos Sudarso III Batu Aji - Minda , Olivia Nelciana; Junianto , Pilifus; Atmojo , Agus Sekti Susila (Tractare: Jurnal Ekonomi-Manajemen, 2025)
ABSTRACT This study aims to determine the influence of promotion, location and price on parents' decision to send their children to SD Yos Sudarso III Batu Aji both partially and simultaneously. This study used a quantitative method by distributing questionnaires to 62 parents of students who sent their children to SD Yos Sudarso III Batu Aji. Data processing in this study uses SPSS version 26. The results of the processing of promotional variable data found that the calculation of 3.009 > ttable of 1.669 with a significance level of 0.004 < 0.05, then promotion had a positive and significant effect on the decision of the parents. The location variable had a calculation of 1.326 < a table of 1.669 with a significance level of 0.190 > 0.05, so the location did not have a positive and significant effect on the decision of the person who knew. The price variable has a calculation of 3.272 > a table of 1.669 with a significance level of 0.002 < 0.05, so the price has a positive and significant effect on the decision of the person who knows. From the f test, it is known that the value of f calculated for promotion, location, and price is 40.896 > f table 2.75 with a significance level of 0.000 < 0.05. From the R2 test, it was found that promotion, location and price contributed 67.9% to parental decision, while the remaining 32.1% of parental decision variables were influenced by other independent variables that were not explained in this study. Year 2025